Social networks, Migrants and Densification. - Mphatsoe, Pulane (UNIVERSITY OF WITWATERSRAND FACULTY OF ENGINEERING & THE BUILT ENVIRONMENT, 2016)
The ambiguous nature of cities has long been discussed by many scholars. Cities are both spaces of opportunity and abject poverty; connectivity to global circuits of goods, people and ideas, yet concurrently contain spaces of marginalisation (Kihato, 2009). The increase in backyard dwellings over the years has highlighted the high demand, and low supply for low-income housing in Johannesburg where many South Africans and international migrants relocate to for greater opportunities. This research report aims to document the relationship between backyard densification and the strategies of integration of migrants into their new host society. These experiences will be documented on the basis of social networks and interaction between the migrants and the locals. The urban form associated with backyard living provides a proximity which fosters intentioned and unintended interaction between neighbours. Backyard densification facilitates access and sustainability of social networks used by migrant women. These social networks play a significant role in the post migratory experiences of migrant women living in backyard dwellings in that they offer various types of support such as trading land, financial and emotional support and childcare just name a few. This research forms part of a greater study on resilient densification in Johannesburg, and though its scope is limited, I hope it will stir up further research pertaining to migration, gender and social networks.
How do migrant women access and sustain social networks in the context of backyard densification in Bram Fischerville?
How do migrant women access and sustain social networks in the context of backyard densification in Bram Fischerville?
Honours Research Report 2016.